2011
DOI: 10.1152/ajpendo.00038.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hyperketonemia increases monocyte adhesion to endothelial cells and is mediated by LFA-1 expression in monocytes and ICAM-1 expression in endothelial cells

Abstract: Rains JL, Jain SK. Hyperketonemia increases monocyte adhesion to endothelial cells and is mediated by LFA-1 expression in monocytes and ICAM-1 expression in endothelial cells. Am J Physiol Endocrinol Metab 301: E298 -E306, 2011. First published May 3, 2011 doi:10.1152/ajpendo.00038.2011.-Frequent episodes of hyperketonemia are associated with a higher incidence of vascular disease. The objective of this study was to examine the hypothesis that hyperketonemia increases monocyte-endothelial cell (EC) adhesion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…16 Our previous work has shown that hyperketonemia leads to adhesion molecule expression and adhesion of monocytes to endothelial cells via LFA-1/ICAM-1 interactions. 15 This study also reported that AA induced chemokine monocyte chemoattractant protein-1 (MCP-1) and IL-8 secretion in monocytes and endothelial cells, both of which play a dominant role in atherogenesis processes. 31 The literature suggests that NF-kB plays a major role in regulating the transcription of inflammatory genes whereas MAPKs regulate both the transcription and the stability of mRNA transcripts.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…16 Our previous work has shown that hyperketonemia leads to adhesion molecule expression and adhesion of monocytes to endothelial cells via LFA-1/ICAM-1 interactions. 15 This study also reported that AA induced chemokine monocyte chemoattractant protein-1 (MCP-1) and IL-8 secretion in monocytes and endothelial cells, both of which play a dominant role in atherogenesis processes. 31 The literature suggests that NF-kB plays a major role in regulating the transcription of inflammatory genes whereas MAPKs regulate both the transcription and the stability of mRNA transcripts.…”
Section: Discussionmentioning
confidence: 85%
“…These results suggest that NF-kB may be the major transcription factor involved in upregulation of other inflammatory biomarkers that have previously been shown to be influenced by hyperketonemic conditions, such as ICAM-1, TNF-a, and IL-6. 15,17,29 Because ICAM-1 is a well-documented NF-kB target gene and is upregulated in inflammatory condition, [35][36][37] it is reasonable to speculate that NF-kB is involved in the regulation of AA-induced ICAM-1 expression. NF-kB is a well-defined redox-sensitive transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocyte-Endothelial Cells Adhesion Assay-Assay was performed as described previously (17). HUVECs were plated and allowed to grow to confluent monolayers.…”
Section: Methodsmentioning
confidence: 99%